DETERMINATION OF HEAVY METALS CONCENTRATIONS IN DUST ON ISLAMABAD HIGHWAY - Faiz, Y.; Javed, M. T.; Farooq, A.; Chaudhary, M. M.; Waheed, K.; Siddique, N. (The Nucleus, 2020)
Street dust is generally composed of automobile exhaust gas originated particles and wind-transported particles. Heavy metals, such as Pb, Cu, Mn, Zn, Cd, Co and Ni are noteworthy for environmental pollution and are found in street dust. Fifteen street dust and two soil samples were collected from six different localities on Islamabad highway, which is a 25 km long road connecting Rawalpindi, a major city of Pakistan to the federal capital, Islamabad. Samples were prepared by the Leeds Public Analyst method. The samples were analyzed for Cu and Zn using AAS. Analysis was also carried out by Instrumental Neutron Activation Analysis using the sample in solid form. The initial results for a sample at Zero Point are presented in this paper. From these initial results it was found that Cu is above permissible limits.